β-Adrenergic regulation requires direct anchoring of PKA to cardiac Ca(V)1.2 channels via a leucine zipper interaction with A kinase-anchoring protein 15 - Hulme, Joanne T. (National Academy of Sciences, 2003)
Activation of β-adrenergic receptors and consequent phosphorylation by cAMP-dependent protein kinase A (PKA) greatly increases the L-type Ca(2+) current through Ca(V)1.2 channels in isolated cardiac myocytes. A kinase-anchoring protein 15 (AKAP15) coimmunoprecipitates with Ca(V)1.2 channels isolated from rat heart membrane extracts and transfected cells, and it colocalizes with Ca(V)1.2 channels and PKA in the transverse tubules of isolated ventricular myocytes. Site-directed mutagenesis studies reveal that AKAP15 directly interacts with the distal C terminus of the cardiac Ca(V)1.2 channel via a leucine zipper-like motif. Disruption of PKA anchoring to Ca(V)1.2 channels via AKAP15 using competing peptides markedly inhibits the β-adrenergic regulation of Ca(V)1.2 channels via the PKA pathway in ventricular myocytes. These results identify a conserved leucine zipper motif in the C terminus of the Ca(V)1 family of Ca(2+) channels that directly anchors an AKAP15-PKA signaling complex to ensure rapid and efficient regulation of L-type Ca(2+) currents in response to β-adrenergic stimulation and local increases in cAMP.